Enhancing Students’ Cultural Competence through Analysis of Visual Artworks - Esanova Lobar Kulmurotovna (NEW SCIENTIFIC PERSPECTIVES AT THE INTERSECTION OF LANGUAGE, CULTURE, AND TECHNOLOGY, 2025)
Abstract: This article examines strategies for developing students’ cultural competence through the analysis of visual artworks. It highlights pedagogical approaches that integrate critical thinking, reflective analysis, and interactive learning to cultivate aesthetic perception, creative skills, and cultural awareness. The study emphasizes the role of visual arts education in fostering both artistic literacy and socio-cultural understanding in students.